The Calligraphy of the Plan - Zaha Hadid (Oz, 1987)
The following is excerpted from a telephone interview with Zaha Hadid. Work began with a shipwreck. It started with a premise that the modern projects have yet to begin. In the earlier times, the reference to the Russian avant garde was a very important beginning, not because of the Russian exuberance and dynamics, but because of the Russian's implications that architecture should be injected with a program.